2005
DOI: 10.1161/circulationaha.104.529404
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Maxi-K + Channel β 1 -Subunit and Altered Vasoregulation in Hypoxia

Abstract: Background-Hypertension, a major cause of cardiovascular morbidity and mortality, can result from chronic hypoxia; however, the pathogenesis of this disorder is unknown. We hypothesized that downregulation of the maxi-K ϩ channel ␤ 1 -subunit by hypoxia decreases the ability of these channels to hyperpolarize arterial smooth muscle cells, thus favoring vasoconstriction and hypertension. Methods and Results-Lowering O 2 tension produced a decrease of maxi-K ϩ ␤ 1 -subunit mRNA levels in rat (aortic and basilar)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…We used cultured mammalian cardiomyocytes to test whether, as it occurs in vascular smooth muscle cells, 13 maxi-K ␤ 1 -subunit mRNA is also downregulated by hypoxia. Both conventional PCR and Northern blot ( Figure 1A) analyses demonstrated that hypoxia (1% O 2 ) induces a marked downregulation of the ␤ 1 -subunit mRNA in neonatal rat cardiomyocytes.…”
Section: Downregulation Of Cardiac Maxi-k ␤ 1 -Subunit By Low O 2 Tenmentioning
confidence: 99%
See 3 more Smart Citations
“…We used cultured mammalian cardiomyocytes to test whether, as it occurs in vascular smooth muscle cells, 13 maxi-K ␤ 1 -subunit mRNA is also downregulated by hypoxia. Both conventional PCR and Northern blot ( Figure 1A) analyses demonstrated that hypoxia (1% O 2 ) induces a marked downregulation of the ␤ 1 -subunit mRNA in neonatal rat cardiomyocytes.…”
Section: Downregulation Of Cardiac Maxi-k ␤ 1 -Subunit By Low O 2 Tenmentioning
confidence: 99%
“…This is in accord with a previous publication from our laboratory reporting that the decrease of ␤ 1 -subunit mRNA levels induced by hypoxia in vascular smooth muscle alters the function of native maxi-K channels in a way compatible with a reduced ␤ 1 protein expression. 13 The mechanism underlying the O 2 tension-dependent ␤ 1 -subunit gene repression was unknown. We have shown that it occurs at the transcriptional level and is mimicked by DMOG and cobalt, inhibitors of prolyl hydroxylases.…”
Section: Hif-2␣-dependent Hypoxic Downregulation Of the ␤ 1 -Subunit mentioning
confidence: 99%
See 2 more Smart Citations
“…BK Ca -type channels have diverse physiological roles; for example, the β1 subunit in SMCs plays a vital role in coupling Ca 2+ influx with BK Ca currents responsible for hypertension. [11][12][13] The openers of BK Catype channels, especially of the mSlo+β1 channel, have received a great deal of attention attributable to the fact that they can be used to treat various cardiovascular diseases. Up to now, no peptidyl opener of BK Ca -mSlo+β1 channels has been reported, Abstract-Human β-defensin 2 (HBD2) is a cysteine-rich cationic antimicrobial peptide known for its important role in innate immune system.…”
Section: +mentioning
confidence: 99%